Pulmonary Blood Volume Measured by Dual-Energy Computed Tomography Can Help Distinguish Patients With Pulmonary Hypertension - Rezaei-Kalantari, Kiara; Samimi, Kaveh; Zomorodian, Hamid; Bakhshandeh, Hooman; Jafari, Maryam; Farahmand, Ali Mohammad; Pourseyedian, Taleb; Sharifian, Maedeh; Qanadli, Salah Dine (Frontiers in Cardiovascular Medicine, 2022)
Purpose: To evaluate the correlation between whole lung enhancement (WLE) and pulmonary blood volume (PBV) obtained through dual energy computed tomography pulmonary angiography (DECTPA) and echocardiography-derived systolic pulmonary arterial pressure (SPAP). Methods: Sixty-eight patients who underwent DECTPA were enrolled to the study after giving informed consent. A transthoracic echocardiography was performed for all the subjects within 48 hours of their DECTPA study to measure SPAP. The correlation of the two DECTPA-derived parameters, WLE and PBV, with SPAP was assessed. In addition, the predictive strength of these parameters was compared with that of traditional computed tomography (CT) signs of pulmonary hypertension (PH). Results: The SPAP value showed a moderate correlation with main pulmonary artery (MPA) diameter (r=0.48, P<0.001), while having a weak correlation with WLE (r=-0.33, P=0.007), PBV (r=-0.31, P=0.01) and MPA/ascending aorta (MPA/AA) ratio (r=0.26, P=0.03). On regression analysis, MPA diameter (B± SE: 1.8± 0.6, P=0.004) and WLE (B± SE: -0.5 ± 0.3, P=0.042) had significant association with SPAP. In addition, SPAP≥30 mmHg was related to the right to left ventricular diameter (RV/LV) ratio [OR(CI95%): 24.39(1.3- 573.2), P=0.04] and reversely associated with PBV [OR(CI95%): 0.96(0.93-0.98), P=0.005]. Acquired cutoff value of 83% for PBV showed sensitivity and specificity of 73% to identify SPAP≥ 30 mmHg (AUC (CI95%):0.727(0.588-0.866), P=0.008). Conclusions: Automated postprocessing calculation of iodine distribution analysis by DECTPA could be considered as an adjunctive tool to investigate for PH.